Drug solution, drug solution container
By adding titanium, iron, aluminum oxide particles and ions of specific proportions and particle sizes to the chemical solution, the metal residual defects when the chemical solution comes into contact with the silicon substrate are solved, and the quality of semiconductor manufacturing is improved.
Patent Information
- Application Number
- JP2023220184
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-08-21
- Filing Date
- 2023-12-27
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2039-08-16
AI Technical Summary
When existing chemical solutions come into contact with silicon substrates or silicon oxide substrates, they can easily lead to metal residual defects, affecting the quality of the semiconductor manufacturing process.
A chemical solution is used that contains a specific proportion of titanium oxide particles and titanium ions, iron oxide particles and iron ions, aluminum oxide particles and aluminum ions and other metal components, as well as a certain concentration of organic solvents. By controlling the proportion and particle size of these components, metal residual defects are reduced.
The metal residual defects in the chemical solution when contacting the silicon substrate or silicon oxide substrate are significantly reduced, and the quality and reliability of the semiconductor manufacturing process are improved.
Smart Images

Figure 0007629083000001 
Figure 0007629083000002 
Figure 0007629083000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a drug solution and a drug solution container. [Background technology]
[0002] During the manufacture of semiconductor devices by a wiring formation process including photolithography, chemical solutions containing water and / or organic solvents are used as pre-wet solutions, resist solutions (compositions for forming resist films), developing solutions, rinsing solutions, stripping solutions, chemical mechanical polishing (CMP) slurries, and post-CMP cleaning solutions, or as diluting solutions thereof. In recent years, advances in photolithography technology have led to the advancement of finer patterns. As a method for finer patterns, attempts have been made to form patterns using ultraviolet light, KrF excimer lasers, ArF excimer lasers, and EUV (extreme ultraviolet) as exposure light sources. As the patterns to be formed become finer, the above-mentioned chemicals used in this process are required to have a higher defect suppression capability.
[0003] As for chemical liquids used in conventional pattern formation, Patent Document 1 discloses "a method for producing an organic processing liquid for patterning of chemically amplified resist films, which is capable of reducing particle generation in pattern formation technology (paragraph
[0010] )." [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2015-084122 A Summary of the Invention [Problem to be solved by the invention]
[0005] Meanwhile, in recent years, there has been a demand for chemical solutions that are less likely to cause metal residue defects on a silicon substrate or a silicon substrate with a silicon oxide film (a silicon substrate whose surface is covered with a silicon oxide film) when the chemical solution is brought into contact with the silicon substrate or the silicon substrate with a silicon oxide film. An object of the present invention is to provide a chemical solution that is less likely to cause metal residue defects when brought into contact with a silicon substrate or a silicon substrate with a silicon oxide film. Another object of the present invention is to provide a drug solution container. [Means for solving the problem]
[0006] As a result of intensive research by the present inventors to solve the above problems, they have found that the above problems can be solved by the following configuration.
[0007] (1) A chemical solution containing an organic solvent and a metal component, The metal component contains titanium oxide particles and titanium ions, The mass ratio of the titanium oxide particle content to the titanium ion content is 10 0 ~10 12 That is, liquid medicine. (2) The chemical solution according to (1), wherein the content of titanium ions is 0.10 to 100 ppt by mass relative to the total mass of the chemical solution. (3) The chemical solution according to (1) or (2), in which the content of titanium oxide particles is 5% by mass or more and less than 99% by mass with respect to the content of titanium components in the metal components. (4) The chemical solution according to any one of (1) to (3), wherein the proportion of titanium oxide particles having a particle size of 0.5 to 17 nm is 60% by mass or more and less than 98% by mass. (5) The metal component contains iron ions, The chemical solution according to any one of (1) to (4), wherein the content of iron ions is 0.10 to 100 ppt by mass relative to the total mass of the chemical solution. (6) The metal component contains iron oxide particles; The chemical solution according to any one of (1) to (5), wherein the content of the iron oxide particles is 5% by mass or more and less than 99% by mass with respect to the content of the iron component in the metal component. (7) The metal component contains iron oxide particles; The chemical solution according to any one of (1) to (6), wherein the proportion of particles having a particle size of 0.5 to 17 nm among the iron oxide particles is 60% by mass or more and less than 98% by mass. (8) The metal component contains iron oxide particles and iron ions, The mass ratio of the iron oxide particle content to the iron ion content is 10 0 ~10 12 The drug solution according to any one of (1) to (7), (9) The metal component contains aluminum ions, The chemical solution according to any one of (1) to (8), wherein the content of aluminum ions is 0.10 to 100 ppt by mass relative to the total mass of the chemical solution. (10) The metal component contains aluminum oxide particles, The chemical solution according to any one of (1) to (9), wherein the content of the aluminum oxide particles is 5% by mass or more and less than 99% by mass with respect to the content of the aluminum component in the metal component. (11) The metal component contains aluminum oxide particles, The chemical solution according to any one of (1) to (10), wherein the proportion of aluminum oxide particles having a particle size of 0.5 to 17 nm is 60% by mass or more and less than 98% by mass. (12) The metal component contains aluminum oxide particles and aluminum ions, The mass ratio of the content of aluminum oxide particles to the content of aluminum ions is 10 0 ~10 12 The drug solution according to any one of (1) to (11), (13) The metal component contains copper oxide particles; The chemical solution according to any one of (1) to (12), wherein the content of the copper oxide particles is 5% by mass or more and less than 99% by mass with respect to the content of the copper component in the metal component. (14) The metal component contains copper oxide particles; The chemical solution according to any one of (1) to (13), wherein the proportion of copper oxide particles having a particle size of 0.5 to 17 nm is 60 mass % or more and less than 98 mass %. (15) The metal component contains copper oxide particles and copper ions; The mass ratio of the copper oxide particles to the copper ion content is 10 0 ~10 12 The drug solution according to any one of (1) to (14), (16) In addition, it contains organic impurities. The chemical solution according to any one of (1) to (15), wherein the content of organic impurities is 1,000 to 100,000 ppt by mass relative to the total mass of the chemical solution. (17) The chemical solution according to any one of (1) to (16), wherein the content of water relative to the total mass of the chemical solution is 500 ppb by mass or less. (18) The chemical solution according to any one of (1) to (17), wherein the organic solvent comprises one or more selected from the group consisting of propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, cyclohexanone, ethyl lactate, propylene carbonate, isopropanol, 4-methyl-2-pentanol, butyl acetate, propylene glycol monoethyl ether, propylene glycol monopropyl ether, methyl methoxypropionate, cyclopentanone, γ-butyrolactone, diisoamyl ether, isoamyl acetate, dimethyl sulfoxide, N-methylpyrrolidone, diethylene glycol, ethylene glycol, dipropylene glycol, propylene glycol, ethylene carbonate, sulfolane, cycloheptanone, 2-heptanone, butyl butyrate, isobutyl isobutyrate, isoamyl ether, and undecane. (19) A drug solution container comprising a container and the drug solution according to any one of (1) to (18) contained in the container. Effect of the Invention
[0008] According to the present invention, it is possible to provide a chemical solution which is less likely to cause metal residue defects when brought into contact with a silicon substrate or a silicon substrate with a silicon oxide film. Further, according to the present invention, a drug solution container can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention will be described in detail below. The following description of the components may be based on a representative embodiment of the present invention, but the present invention is not limited to such an embodiment. In this specification, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits. In the present invention, "ppm" stands for "parts-per-million (10 -6 ) and "ppb" stands for "parts-per-billion (10 -9 )" and "ppt" stands for "parts-per-trillion (10 -12 )" and "ppq" is "parts-per-quadrillion(10 -15 )". In addition, in the description of groups (atomic groups) in the present invention, descriptions that do not indicate whether they are substituted or unsubstituted include groups that do not have a substituent as well as groups that contain a substituent, within the scope of the present invention. For example, a "hydrocarbon group" includes not only a hydrocarbon group that does not have a substituent (unsubstituted hydrocarbon group), but also a hydrocarbon group that contains a substituent (substituted hydrocarbon group). This point is the same for each compound. In the present invention, "radiation" refers to, for example, far ultraviolet light, extreme ultraviolet light (EUV), X-rays, electron beams, etc. In the present invention, light refers to actinic light rays or radiation. Unless otherwise specified, "exposure" in the present invention includes not only exposure to far ultraviolet light, X-rays, EUV, etc., but also drawing with particle beams such as electron beams or ion beams.
[0010] Although the mechanism by which the drug solution of the present invention solves the above problems is not entirely clear, the present inventors speculate on the mechanism as follows: Note that the following mechanism is merely speculation, and even if the effect of the present invention is obtained through a different mechanism, it is still within the scope of the present invention. The present inventors have found that when the chemical solution contains titanium oxide particles and titanium ions, the likelihood of metal residue defects (residues derived from metal components) occurring on a silicon substrate or a silicon substrate with a silicon oxide film (hereinafter, these are also collectively referred to as "specific substrates") varies depending on the mass ratio (mass of titanium oxide particles / mass of oxide ions). More specifically, when the mass ratio is too large, in other words, when the proportion of titanium oxide particles is too high, it is considered that metal residue defects derived from titanium oxide particles are likely to increase on the specific substrate. On the other hand, when the mass ratio is too small, in other words, when the proportion of titanium ions is too high, it is considered that an oxidation-reduction reaction between titanium ions and other metal ions that are less noble than titanium ions is likely to proceed, and particles of other metals (for example, oxide particles of other metals) increase, which is likely to increase metal residue defects on the specific substrate.
[0011] The chemical solution of the present invention is a chemical solution containing an organic solvent and a metal component, the metal component containing titanium oxide particles and titanium ions, and the mass ratio of the content of the titanium oxide particles to the content of the titanium ions is 10 0 ~10 12 It is. The components contained in the drug solution of the present invention will be described in detail below.
[0012] <Organic solvent> The chemical solution of the present invention (hereinafter, also simply referred to as "chemical solution") contains an organic solvent. In this specification, the organic solvent refers to a liquid organic compound contained in an amount exceeding 10,000 ppm by mass per component relative to the total mass of the chemical solution. In other words, in this specification, a liquid organic compound contained in an amount exceeding 10,000 ppm by mass relative to the total mass of the chemical solution corresponds to an organic solvent. In addition, in this specification, the term "liquid" means that the material is liquid at 25° C. and atmospheric pressure.
[0013] The content of the organic solvent in the chemical solution is not particularly limited, but is preferably 98.0% by mass or more, more preferably more than 99.0% by mass, even more preferably 99.90% by mass or more, and particularly preferably more than 99.95% by mass, based on the total mass of the chemical solution. The upper limit is less than 100% by mass. The organic solvent may be used alone or in combination of two or more. When two or more organic solvents are used, the total content is preferably within the above range.
[0014] The type of organic solvent is not particularly limited, and known organic solvents can be used. Examples of the organic solvent include alkylene glycol monoalkyl ether carboxylate, alkylene glycol monoalkyl ether, alkyl lactate, alkyl alkoxypropionate, cyclic lactone (preferably having 4 to 10 carbon atoms), monoketone compound which may have a ring (preferably having 4 to 10 carbon atoms), alkylene carbonate, alkyl alkoxyacetate, alkyl pyruvate, dialkyl sulfoxide, cyclic sulfone, dialkyl ether, monohydric alcohol, glycol, alkyl acetate, and N-alkylpyrrolidone.
[0015] The organic solvent is preferably at least one selected from the group consisting of propylene glycol monomethyl ether acetate (PGMEA), propylene glycol monomethyl ether (PGME), cyclohexanone (CHN), ethyl lactate (EL), propylene carbonate (PC), isopropanol (IPA), 4-methyl-2-pentanol (MIBC), butyl acetate (nBA), propylene glycol monoethyl ether, propylene glycol monopropyl ether, methyl methoxypropionate, cyclopentanone, γ-butyrolactone, diisoamyl ether, isoamyl acetate, dimethyl sulfoxide, N-methylpyrrolidone, diethylene glycol, ethylene glycol, dipropylene glycol, propylene glycol, ethylene carbonate, sulfolane, cycloheptanone, 2-heptanone, butyl butyrate, isobutyl isobutyrate, isoamyl ether, and undecane. Examples of using two or more organic solvents include a combined use of PGMEA and PGME, and a combined use of PGMEA and PC. The type and content of the organic solvent in the chemical solution can be measured using a gas chromatograph mass spectrometer.
[0016] <Metal components> The chemical solution contains a metal component. The metal component is composed of metal-containing particles and metal ions, and for example, the content of the metal component refers to the total content of the metal-containing particles and metal ions. The metal-containing particles may be any particles containing metal atoms, and examples thereof include metal oxide particles, metal nitride particles, and metal particles. Note that the metal particles refer to particles made of metal.
[0017] The metal components contained in the chemical solution include titanium oxide particles and titanium ions. The mass ratio of the titanium oxide particle content to the titanium ion content is 10 0 ~10 12 The mass ratio is preferably 10 to 100, since metal residue defects or composite residue defects described later are less likely to occur on a silicon substrate or a silicon oxide film. 1 ~10 10 is preferred, 10 2 ~10 10 is more preferable, and 10 3 ~10 8 More preferably, 10 3 ~10 7 is particularly preferred.
[0018] The content of titanium ions is not particularly limited, and is often 0.01 to 150 mass ppt. In particular, the content of titanium ions is preferably 0.10 to 100 mass ppt, more preferably 1.0 to 70 mass ppt, relative to the total mass of the chemical solution, in that metal residue defects or composite residue defects described below are less likely to occur on the silicon substrate or silicon oxide film.
[0019] The content of titanium oxide particles is not particularly limited, and is often 1% by mass or more and less than 100% by mass based on the content of titanium components in the metal components. In particular, the content of titanium oxide particles is preferably 5% by mass or more and less than 99% by mass, more preferably 30 to 90% by mass based on the content of titanium components in the metal components, in order to prevent metal residue defects or composite residue defects described later from occurring on the silicon substrate or silicon oxide film. The titanium component is a component that contains titanium atoms, and examples of the titanium component include titanium-containing particles and titanium ions. For example, the content of the titanium component refers to the total content of the titanium-containing particles and titanium ions. The titanium-containing particles may be any particles containing titanium atoms, and examples thereof include titanium oxide particles, titanium nitride particles, and titanium particles. Note that the titanium particles refer to particles made of metallic titanium.
[0020] The proportion of particles having a particle diameter of 0.5 to 17 nm among the titanium oxide particles is not particularly limited, and is often 40% by mass or more and less than 100% by mass. In particular, the proportion of particles having a particle diameter of 0.5 to 17 nm among the titanium oxide particles is preferably 60% by mass or more and less than 98% by mass, more preferably 60 to 95% by mass, in order to prevent metal residue defects or composite residue defects described later from occurring on a silicon substrate or a silicon oxide film.
[0021] The metal component contained in the chemical solution may contain iron ions. The content of iron ions is not particularly limited, and is often 0.01 to 200 mass ppt relative to the total mass of the chemical solution. In particular, the content of iron ions is preferably 0.1 to 100 mass ppt, more preferably 1.0 to 90 mass ppt, relative to the total mass of the chemical solution, in that metal residue defects or composite residue defects described below are less likely to occur on the silicon substrate or silicon oxide film.
[0022] The metal component contained in the chemical solution may contain iron oxide particles. The content of the iron oxide particles is not particularly limited, and is often 1% by mass or more and less than 100% by mass relative to the content of the iron component in the metal component. In particular, the content of the iron oxide particles is preferably 5% by mass or more and less than 99% by mass, and more preferably 10 to 95% by mass, relative to the content of the iron component in the metal component, in order to prevent metal residue defects or composite residue defects described later from occurring on the silicon substrate or silicon oxide film. The iron component is a component that contains iron atoms, and examples of the iron component include iron-containing particles and iron ions. For example, the content of the iron component refers to the total content of the iron-containing particles and iron ions. The iron-containing particles may be any particles containing iron atoms, and examples thereof include iron oxide particles, iron nitride particles, and iron particles. Note that the iron particles refer to particles made of metallic iron.
[0023] The proportion of particles having a particle size of 0.5 to 17 nm among the iron oxide particles is not particularly limited, and is often 40% by mass or more and less than 100% by mass. In particular, the proportion of particles having a particle size of 0.5 to 17 nm among the iron oxide particles is preferably 60% by mass or more and less than 98% by mass, more preferably 60 to 95% by mass, in order to prevent metal residue defects or composite residue defects described later from occurring on a silicon substrate or a silicon oxide film.
[0024] The mass ratio of the content of iron oxide particles to the content of iron ions in the chemical solution is not particularly limited, and is preferably 10 -2 ~10 14 In particular, the above mass ratio is preferably 10 to 150, since metal residue defects or composite residue defects described later are less likely to occur on a silicon substrate or a silicon oxide film. 0 ~10 12 is preferred, 10 2 ~10 10 is more preferable, and 10 3 ~10 8 More preferably, 10 3 ~10 7 is particularly preferred.
[0025] The metal component contained in the chemical solution may contain aluminum ions. The content of aluminum ions is not particularly limited, and is often 0.01 to 200 mass ppt relative to the total mass of the chemical solution. In particular, the content of aluminum ions is preferably 0.1 to 100 mass ppt, more preferably 1.0 to 90 mass ppt, relative to the total mass of the chemical solution, in that metal residue defects or composite residue defects described below are less likely to occur on the silicon substrate or silicon oxide film.
[0026] The metal component contained in the chemical solution may contain aluminum oxide particles. The content of the aluminum oxide particles is not particularly limited, and is often 1 mass% or more and less than 100 mass% based on the content of the aluminum component in the metal component. In particular, the content of the aluminum oxide particles is preferably 5 mass% or more and less than 99 mass%, more preferably 10 to 95 mass%, based on the content of the aluminum component in the metal component, in order to prevent metal residue defects or composite residue defects described later from occurring on the silicon substrate or silicon oxide film. The aluminum component is a component that contains aluminum atoms, and examples of such components include aluminum-containing particles and aluminum ions. For example, the content of the aluminum component refers to the total content of the aluminum-containing particles and aluminum ions. The aluminum-containing particles may be any particles containing aluminum atoms, and examples thereof include aluminum oxide particles, aluminum nitride particles, and aluminum particles. Note that the aluminum particles refer to particles made of metallic aluminum.
[0027] The proportion of aluminum oxide particles having a particle size of 0.5 to 17 nm is not particularly limited, and is often 40% by mass or more and less than 100% by mass. In particular, the proportion of aluminum oxide particles having a particle size of 0.5 to 17 nm is preferably 60% by mass or more and less than 98% by mass, more preferably 60 to 95% by mass, in order to prevent metal residue defects or composite residue defects described later from occurring on a silicon substrate or a silicon oxide film.
[0028] The mass ratio of the content of aluminum oxide particles to the content of aluminum ions in the chemical solution is not particularly limited, and is preferably 10 -2 ~10 14 In particular, the above mass ratio is preferably 10 to 150, since metal residue defects or composite residue defects described later are less likely to occur on a silicon substrate or a silicon oxide film. 0 ~10 12 is preferred, 10 2 ~10 10 is more preferable, and 10 3 ~10 8 More preferably, 10 3 ~10 7 is particularly preferred.
[0029] The metal components contained in the chemical solution may contain metal atom components other than those mentioned above. Examples of other metal atoms include Na (sodium), K (potassium), Ca (calcium), Cu (copper), Mg (magnesium), Mn (manganese), Li (lithium), Cr (chromium), Ni (nickel), and Zr (zirconium).
[0030] The metal component contained in the chemical solution may contain copper oxide particles. The content of the copper oxide particles is not particularly limited, and is often 1% by mass or more and less than 100% by mass relative to the content of the copper component in the metal component. In particular, the content of the copper oxide particles is preferably 5% by mass or more and less than 99% by mass, more preferably 10 to 95% by mass, relative to the content of the copper component in the metal component, in order to prevent metal residue defects or composite residue defects described later from occurring on the silicon substrate or silicon oxide film. The copper component is a component that contains copper atoms, and examples thereof include copper-containing particles and copper ions. For example, the content of the copper component refers to the total content of the copper-containing particles and copper ions. The copper-containing particles may be any particles containing copper atoms, and examples thereof include copper oxide particles, copper nitride particles, and copper particles. Note that the copper particles refer to particles made of metallic copper.
[0031] The proportion of copper oxide particles having a particle size of 0.5 to 17 nm is not particularly limited, and is often 40% by mass or more and less than 100% by mass. In particular, the proportion of copper oxide particles having a particle size of 0.5 to 17 nm is preferably 60% by mass or more and less than 98% by mass, more preferably 60 to 95% by mass, in order to prevent metal residue defects or composite residue defects described later from occurring on a silicon substrate or a silicon oxide film.
[0032] The mass ratio of the copper oxide particles to the copper ions in the chemical solution is not particularly limited, and is preferably 10 -2 ~10 14 In particular, the above mass ratio is preferably 10 to 150, since metal residue defects or composite residue defects described later are less likely to occur on a silicon substrate or a silicon oxide film. 0 ~10 12 is preferred, 10 2 ~10 10 is more preferable, and 10 3 ~10 8 More preferably, 10 3 ~10 7 is particularly preferred.
[0033] The metal components may be metal components that are inevitably contained in each component (raw material) contained in the chemical solution, or metal components that are inevitably contained during the production, storage, and / or transportation of the treatment solution, or may be metal components that are intentionally added.
[0034] The content of the metal component is not particularly limited, but is preferably 10 to 500,000 mass ppt relative to the total mass of the chemical solution, since this makes it less likely that metal residue defects or composite residue defects described below will occur on the silicon substrate or silicon oxide film.
[0035] The types and contents of metal ions and metal-containing particles in the chemical solution can be measured by SP-ICP-MS (Single Nano Particle Inductively Coupled Plasma Mass Spectrometry). Here, the SP-ICP-MS method uses the same equipment as the normal ICP-MS method (inductively coupled plasma mass spectrometry), and only the data analysis is different. Data analysis of the SP-ICP-MS method can be performed using commercially available software. In the ICP-MS method, the content of the metal component to be measured is measured regardless of the form in which it exists. Therefore, the total mass of the metal-containing particles and metal ions to be measured is quantified as the content of the metal component.
[0036] On the other hand, the SP-ICP-MS method can measure the content of metal-containing particles, so the content of metal ions in a sample can be calculated by subtracting the content of metal-containing particles from the content of metal components in the sample. An example of the SP-ICP-MS method device is Agilent 8800 triple quadrupole ICP-MS (inductively coupled plasma mass spectrometry, for semiconductor analysis, option #200) manufactured by Agilent Technologies, and the measurement can be performed by the method described in the Examples. As other devices than those described above, PerkinElmer's NexION350S and Agilent Technologies' Agilent 8900 can also be used.
[0037] In addition, since metal-containing particles of 10 nm or less cannot be measured by SP-ICP-MS, the method described in paragraphs 0015 to 0067 of JP-A No. 2009-188333 (hereinafter also referred to as the "specifying method") is used. Here, the number of 0.5-10 nm particles remaining on the substrate is counted using a specific method, and the conversion value from SNP-ICP-MS for 20 nm particles is used for that count. Since the conversion value differs for each metal, this conversion is performed for each metal. The specific method of conversion is as follows: For example, if the number of 20 nm titanium oxide particles in the chemical solution is 10 by SNP-ICP-MS, and the number of 20 nm titanium oxide particles remaining on the substrate calculated by the specified method is 1, the conversion value is 10. In other words, if the number of 1 nm titanium oxide particles confirmed by the specified method is 100, the conversion value is multiplied by 10 to calculate that there are 1000 particles in the chemical solution (100 particles x 10). The number of particles of 10 nm or less in the present invention is estimated by this conversion method, regardless of the metal.
[0038] <Organic impurities> The chemical solution may contain organic impurities. The content of organic impurities in the chemical solution is not particularly limited, but is preferably 1,000 to 100,000 ppt by mass relative to the total mass of the chemical solution, in that stain-like residue defects described below are less likely to occur on the silicon substrate. The organic impurities refer to organic compounds that are different from organic solvents and are contained in an amount of 10,000 ppm by mass or less relative to the total mass of the organic solvent. In other words, in this specification, organic compounds that are contained in an amount of 10,000 ppm by mass or less relative to the total mass of the organic solvent are considered to be organic impurities and not organic solvents. Organic impurities are often mixed into or added to a chemical solution during the process of purifying a material to be purified to obtain a chemical solution. Examples of such organic impurities include plasticizers, antioxidants, and compounds derived from these (typically decomposition products).
[0039] <Water> The chemical solution may contain water, which is not included in the organic impurities. The water is not particularly limited, and for example, distilled water, ion-exchanged water, pure water, etc. can be used. Water may be added to the chemical solution, or may be unintentionally mixed into the chemical solution during the manufacturing process of the chemical solution. Examples of cases where water is unintentionally mixed during the manufacturing process of the chemical solution include, but are not limited to, cases where water is contained in a raw material (e.g., an organic solvent) used in the manufacturing of the chemical solution, and cases where water is mixed during the manufacturing process of the chemical solution (e.g., contamination).
[0040] The water content in the chemical solution is not particularly limited, but is preferably 2.0 mass% or less, more preferably 500 mass ppb or less, based on the total mass of the chemical solution. The lower limit is not particularly limited, but may be 0 mass%. The water content in the chemical solution refers to the water content measured using an apparatus that uses the Karl Fischer moisture content measurement method as the measurement principle.
[0041] <Chemical Uses> The chemical solution of the present invention is preferably used in the manufacture of semiconductor devices, and in particular, it is preferable to manufacture semiconductor chips using the chemical solution of the present invention. Specifically, in the manufacturing process of semiconductor devices including a lithography process, an etching process, an ion implantation process, a peeling process, and the like, the liquid is used to treat organic matter after the completion of each process or before moving to the next process, and specifically, is suitably used as a pre-wet liquid, a developing liquid, a rinsing liquid, a polishing liquid, and the like. In addition, the chemical liquid may be used as a diluting liquid (in other words, a solvent) for the resin contained in the composition for forming a resist film.
[0042] Furthermore, the above-mentioned chemical solution can be used for purposes other than the manufacture of semiconductor devices, and can also be used as a developer and rinse solution for polyimide, resist for sensors, resist for lenses, and the like. The chemical liquid can also be used as a solvent for medical or cleaning purposes, for example, for cleaning pipes, containers, and substrates (e.g., wafers, glass, etc.). As the above-mentioned cleaning application, it is also preferable to use it as a cleaning liquid (pipe cleaning liquid, container cleaning liquid, etc.) for cleaning pipes, containers, etc. that come into contact with liquids such as the pre-wet liquid described above.
[0043] Among them, the chemical liquid is preferably used for a pre-wetting liquid, a developer, a rinse liquid, a polishing liquid, and a composition for forming a resist film. Among them, when applied to a pre-wetting liquid, a developer, and a rinse liquid, a more excellent effect is exhibited. In particular, when applied to a pre-wetting liquid, a developer, and a rinse liquid in the case where the exposure light source is EUV, a more excellent effect is exhibited. In addition, when applied to a pipe cleaning liquid used for the pipes used for transporting these liquids, a more excellent effect is exhibited.
[0044] <Method of manufacturing chemicals> The method for producing the above-mentioned chemical solution is not particularly limited, and any known production method can be used. Among them, the method for producing the chemical solution preferably includes a filtration step of filtering the material to be purified containing the organic solvent using a filter to obtain the chemical solution, in order to obtain a chemical solution that exhibits a more excellent effect of the present invention.
[0045] The material to be purified used in the filtration step may be procured by purchase or the like, or may be obtained by reacting raw materials. It is preferable that the material to be purified has a low content of impurities. Examples of commercially available products of such materials to be purified include commercially available products called "high purity grade products."
[0046] The method of reacting raw materials to obtain a product to be purified (typically a product to be purified containing an organic solvent) is not particularly limited, and any known method can be used. For example, there is a method of reacting one or more raw materials in the presence of a catalyst to obtain an organic solvent. More specifically, for example, there is a method of reacting acetic acid with n-butanol in the presence of sulfuric acid to obtain butyl acetate; a method of reacting ethylene, oxygen, and water in the presence of Al(C2H5)3 to obtain 1-hexanol; a method of reacting cis-4-methyl-2-pentene in the presence of Ipc2BH (Diisopinocampheylborane) to obtain 4-methyl-2-pentanol; a method of reacting propylene oxide, methanol, and acetic acid in the presence of sulfuric acid to obtain PGMEA (propylene glycol 1-monomethyl ether 2-acetate); a method of reacting acetone and hydrogen in the presence of copper oxide-zinc oxide-aluminum oxide to obtain IPA (isopropyl alcohol); and a method of reacting lactic acid and ethanol to obtain ethyl lactate.
[0047] (Filtration process) The method for producing a drug solution of the present invention preferably includes a filtration step of filtering the target substance using a filter to obtain a drug solution. The method for filtering the target substance using a filter is not particularly limited, but it is preferable to pass the target substance through a filter unit having a housing and a filter cartridge housed in the housing with or without pressure.
[0048] Filter pore size The pore size of the filter is not particularly limited, and a filter having a pore size that is usually used for filtering a product to be purified can be used. In particular, the pore size of the filter is preferably 200 nm or less, more preferably 20 nm or less, even more preferably 10 nm or less, and particularly preferably 5 nm or less, in order to easily control the number of particles (metal particles, etc.) contained in the chemical solution within a desired range. The lower limit is not particularly limited, but generally, 1 nm or more is preferred from the viewpoint of productivity. In this specification, the pore size of the filter means the pore size determined by the bubble point of isopropanol (IPA).
[0049] It is preferable that the pore size of the filter is 5.0 nm or less, since it is easier to control the number of particles contained in the drug solution. Hereinafter, a filter having a pore size of 5.0 nm or less is also referred to as a "micropore filter." The micropore filter may be used alone or together with a filter having another pore size. In particular, it is preferable to use a filter having a larger pore size from the viewpoint of superior productivity. In other words, when two or more filters are used, it is preferable that the pore size of at least one filter is 5.0 nm or less. In this case, clogging of the micropore filter can be prevented by passing the product to be purified, which has been previously filtered through a filter having a larger pore size, through the micropore filter. That is, when one filter is used, the pore size of the filter is preferably 5.0 nm or less, and when two or more filters are used, the pore size of the filter having the smallest pore size is preferably 5.0 nm or less.
[0050] The form of using two or more filters with different pore sizes in sequence is not particularly limited, but includes a method of arranging the filter units described above in sequence along the pipeline through which the purified product is transported. In this case, if the flow rate per unit time of the purified product is to be constant throughout the entire pipeline, a filter with a smaller pore size may be subjected to a larger pressure than a filter with a larger pore size. In this case, it is preferable to arrange a pressure regulating valve and a damper between the filters to make the pressure on the filter with a smaller pore size constant, or to arrange filter units containing the same filter in parallel along the pipeline to increase the filtration area. In this way, the number of particles in the drug solution can be controlled more stably.
[0051] Filter material The material of the filter is not particularly limited, and known materials can be used as the material of the filter.Specifically, in the case of resin, polyamide such as nylon (for example, 6-nylon and 6,6-nylon), polyolefin such as polyethylene and polypropylene, polystyrene, polyimide, polyamideimide, poly(meth)acrylate, polytetrafluoroethylene, perfluoroalkoxyalkane, perfluoroethylenepropene copolymer, ethylene-tetrafluoroethylene copolymer, ethylene-chlorotrifluoroethylene copolymer, polychlorotrifluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyvinyl fluoride, polyvinyl alcohol, polyester, cellulose, cellulose acetate, etc. can be mentioned. Among them, at least one selected from the group consisting of nylon (among which 6,6-nylon is preferred), polyolefin (among which polyethylene is preferred), poly(meth)acrylate, and polyfluorocarbon (among which polytetrafluoroethylene (PTFE) and perfluoroalkoxyalkane (PFA) are preferred) is preferred, in that it has better solvent resistance and the resulting chemical solution has better defect suppression performance. These polymers can be used alone or in combination of two or more. In addition to resin, materials such as diatomaceous earth and glass may also be used. Alternatively, a polymer (such as nylon-grafted UPE) in which polyamide (for example, nylons such as nylon-6 or nylon-6,6) is graft-copolymerized with polyolefin (such as UPE (ultra-high molecular weight polyethylene) described below) may be used as the filter material.
[0052] The filter may be a surface-treated filter. The method of surface treatment is not particularly limited, and known methods can be used. Examples of the surface treatment method include chemical modification treatment, plasma treatment, hydrophobic treatment, coating, gas treatment, and sintering.
[0053] The plasma treatment is preferred because it makes the filter surface hydrophilic. The water contact angle on the filter surface that has been hydrophilized by plasma treatment is not particularly limited, but the static contact angle at 25°C measured with a contact angle meter is preferably 60° or less, more preferably 50° or less, and even more preferably 30° or less.
[0054] As the chemical modification treatment, a method of introducing an ion exchange group into the filter is preferable. That is, the filter is preferably a filter having an ion exchange group. Examples of the ion exchange group include a cation exchange group and an anion exchange group, examples of the cation exchange group include a sulfonic acid group, a carboxyl group, and a phosphate group, and examples of the anion exchange group include a quaternary ammonium group. There are no particular limitations on the method for introducing the ion exchange group into the filter, but examples of the method include a method in which a compound containing an ion exchange group and a polymerizable group is reacted with the filter to typically perform grafting.
[0055] The method for introducing ion exchange groups is not particularly limited, but may be to irradiate the filter with ionizing radiation (alpha rays, beta rays, gamma rays, X-rays, electron beams, etc.) to generate active moieties (radicals). After this irradiation, the filter is immersed in a monomer-containing solution to graft polymerize the monomer onto the filter. As a result, the polymer obtained by polymerization of the monomer is grafted onto the filter. The generated polymer is contacted with a compound containing an anion exchange group or a cation exchange group to introduce ion exchange groups into the polymer.
[0056] The filter may also be constructed by combining a woven or nonwoven fabric on which ion exchange groups have been formed by radiation-induced graft polymerization with a conventional filtering material such as glass wool, woven or nonwoven fabric.
[0057] By using a filter having an ion exchange group, the content of metal-containing particles and metal ions in the chemical solution can be easily controlled to a desired range. The material constituting the filter having an ion exchange group is not particularly limited, but examples thereof include polyfluorocarbons and materials in which ion exchange groups are introduced into polyolefins, and materials in which ion exchange groups are introduced into polyfluorocarbons are more preferable. The pore size of the filter having an ion exchange group is not particularly limited, but is preferably 1 to 30 nm, more preferably 5 to 20 nm. The filter having an ion exchange group may also serve as the filter having the smallest pore size as described above, or may be used separately from the filter having the smallest pore size. Among them, the filtration step preferably uses a filter having an ion exchange group and a filter having no ion exchange group and having the smallest pore size, in order to obtain a chemical solution that exhibits a more excellent effect of the present invention. The material of the filter having the minimum pore size already described is not particularly limited, but from the viewpoint of solvent resistance and the like, generally, at least one selected from the group consisting of polyfluorocarbons and polyolefins is preferred, and polyolefins are more preferred.
[0058] Therefore, the filters used in the filtration step may be two or more filters made of different materials. For example, two or more filters selected from the group consisting of filters made of polyolefins, polyfluorocarbons, polyamides, and filters made of these materials having ion exchange groups introduced therein may be used.
[0059] -Porous structure of the filter The pore structure of the filter is not particularly limited and may be appropriately selected depending on the components in the product to be purified. In this specification, the pore structure of the filter means the pore size distribution, the positional distribution of the pores in the filter, the shape of the pores, etc., and can typically be controlled by the manufacturing method of the filter. For example, a porous membrane can be obtained by sintering powder of resin or the like, and a fibrous membrane can be obtained by forming the membrane by methods such as electrospinning, electroblowing, and meltblowing, each of which has a different pore structure.
[0060] By "porous membrane" is meant a membrane that retains components of a product, such as gels, particles, colloids, cells, and poly-oligomers, but allows components substantially smaller than the pores to pass through the pores. Retention of components of a product by a porous membrane may depend on operating conditions, such as face velocity, use of surfactants, pH, and combinations thereof, and may depend on the pore size, structure, and size and structure of the particles to be removed (such as hard particles or gels).
[0061] When the product to be purified contains negatively charged particles, polyamide filters act as non-sieving membranes to remove such particles. Exemplary non-sieving membranes include, but are not limited to, nylon membranes such as nylon-6 membranes and nylon-6,6 membranes. It is noted that, as used herein, "non-sieving" retention mechanisms refer to retention that occurs due to mechanisms such as obstruction, diffusion and adsorption that are not related to the pressure drop or pore size of the filter.
[0062] Non-sieving retention includes retention mechanisms such as obstruction, diffusion and adsorption that remove target particles in the product regardless of the pressure drop of the filter or the pore size of the filter. Adsorption of particles to the filter surface can be mediated, for example, by intermolecular van der Waals and electrostatic forces. Obstruction effects occur when particles moving through a non-sieving membrane layer with a tortuous path cannot be redirected quickly enough to avoid contact with the non-sieving membrane. Particle transport by diffusion results primarily from random or Brownian motion of small particles, which creates a certain probability of the particles colliding with the filter media. Non-sieving retention mechanisms can be active when there is no repulsive force between the particles and the filter.
[0063] UPE (ultra-high molecular weight polyethylene) filters are typically sieving membranes, which refers to membranes that capture particles primarily through a sieving retention mechanism or that are optimized for capturing particles through a sieving retention mechanism. Typical examples of sieving membranes include, but are not limited to, polytetrafluoroethylene (PTFE) membranes and UPE membranes. The "sieve retention mechanism" refers to the retention of particles that are larger than the pore size of the porous membrane. Sieve retention is improved by forming a filter cake (an agglomeration of particles to be removed on the membrane surface). The filter cake effectively performs the function of a secondary filter.
[0064] The material of the fiber membrane is not particularly limited as long as it is a polymer capable of forming a fiber membrane. Examples of the polymer include polyamides. Examples of the polyamide include nylon 6 and nylon 6,6. The polymer forming the fiber membrane may be poly(ethersulfone). When the fiber membrane is on the primary side of the porous membrane, it is preferable that the surface energy of the fiber membrane is higher than that of the polymer that is the material of the porous membrane on the secondary side. An example of such a combination is when the material of the fiber membrane is nylon and the porous membrane is polyethylene (UPE).
[0065] The method for producing the fiber membrane is not particularly limited, and any known method can be used, including, for example, electrospinning, electroblowing, and meltblowing.
[0066] The pore structure of the porous membrane (e.g., porous membranes containing UPE, PTFE, etc.) is not particularly limited, but examples of the pore shape include lace-like, string-like, and node-like. The distribution of pore sizes in the porous membrane and the distribution of their positions in the membrane are not particularly limited. The size distribution may be smaller and the distribution positions in the membrane may be symmetric. The size distribution may be larger and the distribution positions in the membrane may be asymmetric (the above membrane is also called "asymmetric porous membrane"). In an asymmetric porous membrane, the size of the pores changes in the membrane, and typically the pore size increases from one surface of the membrane to the other surface of the membrane. In this case, the surface on the side where there are more pores with large pore sizes is called the "open side", and the surface on the side where there are more pores with small pore sizes is also called the "tight side". Asymmetric porous membranes include, for example, membranes in which the pore size is smallest at a position within the thickness of the membrane (also called "hourglass shaped").
[0067] With an asymmetric porous membrane, the primary side has larger pore size, in other words the primary side is the open side, creating a pre-filtration effect.
[0068] The porous membrane may include a thermoplastic polymer such as PESU (polyethersulfone), PFA (perfluoroalkoxyalkane, a copolymer of tetrafluoroethylene and perfluoroalkoxyalkane), polyamide, and polyolefin, or may include polytetrafluoroethylene, etc. Among them, ultra-high molecular weight polyethylene is preferable as the material for the porous film. Ultra-high molecular weight polyethylene means a thermoplastic polyethylene having an extremely long chain, and preferably has a molecular weight of at least one million, typically 2 to 6 million.
[0069] The filter used in the filtration step may be two or more filters having different pore structures, or a porous membrane filter and a fiber membrane filter may be used in combination. A specific example is a method using a nylon fiber membrane filter and a UPE porous membrane filter.
[0070] It is also preferable to thoroughly wash the filter before use. When an unwashed filter (or a filter that has not been sufficiently washed) is used, impurities contained in the filter are likely to be carried over into the chemical solution.
[0071] As described above, the filtration process according to an embodiment of the present invention may be a multistage filtration process in which the material to be purified is passed through two or more types of filters that differ in at least one aspect selected from the group consisting of filter material, pore size, and pore structure. The material to be purified may be passed through the same filter multiple times, or through multiple filters of the same type.
[0072] In preparing the drug solution of the present invention, it is preferable to use a filter (metal component removing filter) capable of selectively removing metal components (particularly metal ions) such as "Purasol SN 200 nm" as a filter.
[0073] The material of the liquid-contacting part of the purification device used in the filtration process (meaning the inner wall surface that may come into contact with the product to be purified and the chemical liquid) is not particularly limited, but is preferably made of at least one material selected from the group consisting of non-metallic materials (such as fluororesins) and electrolytically polished metallic materials (such as stainless steel) (hereinafter, these are also collectively referred to as "corrosion-resistant materials"). For example, when the liquid-contacting part of a production tank is made of a corrosion-resistant material, it can be meant that the production tank itself is made of a corrosion-resistant material, or the inner wall surface of the production tank is covered with a corrosion-resistant material.
[0074] The non-metallic material is not particularly limited, and any known material can be used. Examples of non-metallic materials include, but are not limited to, at least one selected from the group consisting of polyethylene resin, polypropylene resin, polyethylene-polypropylene resin, and fluorine-based resin (e.g., tetrafluoroethylene resin, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer resin, tetrafluoroethylene-hexafluoropropylene copolymer resin, tetrafluoroethylene-ethylene copolymer resin, trifluorochloroethylene-ethylene copolymer resin, vinylidene fluoride resin, trifluorochloroethylene copolymer resin, and vinyl fluoride resin).
[0075] The metal material is not particularly limited, and any known material can be used. The metal material may be, for example, a metal material in which the total content of chromium and nickel is more than 25 mass% relative to the total mass of the metal material, and more preferably 30 mass% or more. The upper limit of the total content of chromium and nickel in the metal material is not particularly limited, but is generally preferably 90 mass% or less. Examples of metallic materials include stainless steel and nickel-chromium alloys.
[0076] The stainless steel is not particularly limited, and known stainless steels can be used. Among them, an alloy containing 8% or more by mass of nickel is preferable, and an austenitic stainless steel containing 8% or more by mass of nickel is more preferable. Examples of austenitic stainless steel include SUS (Steel Use Stainless) 304 (Ni content 8% by mass, Cr content 18% by mass), SUS304L (Ni content 9% by mass, Cr content 18% by mass), SUS316 (Ni content 10% by mass, Cr content 16% by mass), and SUS316L (Ni content 12% by mass, Cr content 16% by mass).
[0077] The nickel-chromium alloy is not particularly limited, and any known nickel-chromium alloy can be used. Among them, a nickel-chromium alloy having a nickel content of 40 to 75 mass % and a chromium content of 1 to 30 mass % is preferable. Examples of nickel-chromium alloys include Hastelloy (trade name, the same applies below), Monel (trade name, the same applies below), and Inconel (trade name, the same applies below). More specifically, examples of nickel-chromium alloys include Hastelloy C-276 (Ni content: 63 mass%, Cr content: 16 mass%), Hastelloy-C (Ni content: 60 mass%, Cr content: 17 mass%), and Hastelloy C-22 (Ni content: 61 mass%, Cr content: 22 mass%). Furthermore, the nickel-chromium alloy may further contain boron, silicon, tungsten, molybdenum, copper, cobalt, and the like, in addition to the above-mentioned alloy, as required.
[0078] The method for electrolytically polishing the metal material is not particularly limited, and any known method can be used, such as those described in paragraphs
[0011] to
[0014] of JP 2015-227501 A and paragraphs
[0036] to
[0042] of JP 2008-264929 A.
[0079] It is presumed that the chromium content in the surface passive layer of the metal material is higher than the chromium content in the parent phase due to electrolytic polishing, and therefore, it is presumed that metal-containing particles are less likely to flow out into the product to be refined when a refining device with a liquid-contacting part made of an electrolytically polished metal material is used. The metal material may be buffed. The method of buffing is not particularly limited, and known methods can be used. The size of the polishing grains used for the buffing is not particularly limited, but #400 or less is preferable because it tends to reduce the unevenness of the surface of the metal material. The buffing is preferably performed before the electrolytic polishing.
[0080] (Other processes) The method for producing the chemical solution may further include a step other than the filtration step, such as a distillation step, a reaction step, and a static electricity removal step.
[0081] (Distillation process) The distillation step is a step of distilling a purification target material containing an organic solvent to obtain a distilled purification target material. The method of distilling the purification target material is not particularly limited, and a known method can be used. A typical example is a method in which a distillation column is placed on the primary side of a purification device subjected to a filtration step, and the distilled purification target material is introduced into a production tank. In this case, the liquid-contacting parts of the distillation column are not particularly limited, but are preferably made of the corrosion-resistant materials already explained.
[0082] (Reaction process) The reaction step is a step of reacting raw materials to produce a product to be purified that contains an organic solvent as a reactant. The method of producing the product to be purified is not particularly limited, and a known method can be used. A typical example is a method in which a reaction tank is disposed on the primary side of a production tank (or a distillation column) of a purification device that is subjected to a filtration step, and the reactant is introduced into the production tank (or the distillation column). In this case, the liquid-contacting parts of the production tank are not particularly limited, but are preferably made of the corrosion-resistant materials already described.
[0083] (static elimination process) The charge removal step is a step of removing static electricity from the material to be purified to reduce the charged potential of the material to be purified. The method for removing static electricity is not particularly limited, and any known method can be used. For example, the method for removing static electricity includes contacting the product to be purified with a conductive material. The contact time for contacting the material to be purified with the conductive material is preferably 0.001 to 60 seconds, more preferably 0.001 to 1 second, and even more preferably 0.01 to 0.1 seconds. Examples of the conductive material include stainless steel, gold, platinum, diamond, and glassy carbon. As a method for contacting the material to be purified with a conductive material, for example, a grounded mesh made of a conductive material is placed inside the pipeline and the material to be purified is passed through the mesh.
[0084] It is preferable that the purification of the target substance, the opening of the container, the cleaning of the container and the device, the storage of the solution, and the analysis, which are associated with the purification, are all performed in a clean room. The clean room is preferably a clean room with a cleanliness of class 4 or higher as defined by the international standard ISO14644-1:2015 established by the International Organization for Standardization. Specifically, it is preferable that the clean room meets any one of ISO class 1, ISO class 2, ISO class 3, and ISO class 4, more preferably ISO class 1 or ISO class 2, and even more preferably ISO class 1.
[0085] The storage temperature of the drug solution is not particularly limited, but a storage temperature of 4°C or higher is preferable because impurities contained in trace amounts in the drug solution are less likely to be eluted, resulting in a more excellent effect of the present invention.
[0086] <Chemical Solution Container> The drug solution produced by the above purification method may be stored in a container until it is used. Such a container and the liquid medicine contained therein are collectively referred to as a liquid medicine container. The liquid medicine is taken out of the stored liquid medicine container and used.
[0087] The container for storing the above-mentioned chemical solution is preferably one that is highly clean inside and has little elution of impurities for use in semiconductor device manufacturing. Specific examples of containers that can be used include the "Clean Bottle" series manufactured by Aicello Chemical Co., Ltd. and the "Pure Bottle" manufactured by Kodama Resin Industry Co., Ltd., but are not limited to these.
[0088] As the container, it is also preferable to use a multi-layer bottle whose inner wall has a six-layer structure made of six types of resin, or a multi-layer bottle whose inner wall has a seven-layer structure made of six types of resin, in order to prevent impurities from being mixed in (contaminated) with the drug solution. Examples of such containers include the containers described in JP 2015-123351 A.
[0089] The liquid-contacting portion of the container may be made of the corrosion-resistant material already described (preferably electrolytically polished stainless steel or fluororesin) or glass. In order to obtain a better effect of the present invention, it is preferable that 90% or more of the area of the liquid-contacting portion is made of the above material, and it is more preferable that the entire liquid-contacting portion is made of the above material.
[0090] The porosity within the container of the drug solution container is preferably 2 to 80% by volume, more preferably 2 to 50% by volume, and even more preferably 5 to 30% by volume. The porosity is calculated according to formula (1). Formula (1): Porosity = {1-(Volume of drug solution in container / Volume of container)} x 100 The container volume is synonymous with the internal volume (capacity) of the container. By setting the porosity within this range, it is possible to ensure storage stability by limiting contamination such as impurities. EXAMPLES
[0091] The present invention will be described in more detail below based on examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the following examples.
[0092] In preparing the chemical solutions in the Examples and Comparative Examples, handling of containers, preparation, filling, storage and analysis of the chemical solutions were all carried out in a clean room that met ISO class 2 or 1 standards.
[0093] (Filter) The following filters were used: "Purasol SN 200nm": UPE membrane (material) manufactured by Entegris, pore size 200nm "PP 200nm": Polypropylene filter, Entegris, pore size 200nm ·“Purasol SP 200nm”: UPE membrane (material) manufactured by Entegris, pore diameter 200nm "Octolex 5nm": UPE nylon filter graft, Entegris, pore size 5nm "IEX 15nm": Ion exchange resin filter, Entegris, pore size 15nm "IEX 16nm": Ion exchange resin filter, Entegris, pore size 16nm "IEX 50nm": Ion exchange resin filter, Entegris, pore size 50nm "IEX 200nm": Ion exchange resin filter, Entegris, pore size 200nm "PTFE 5nm": Polytetrafluoroethylene filter, Entegris, pore size 5nm "PTFE 7nm": Polytetrafluoroethylene filter, Entegris, pore size 7nm "PTFE 10nm": Polytetrafluoroethylene filter, Entegris, pore size 10nm "PTFE 20nm": Polytetrafluoroethylene filter, Entegris, pore size 20nm "Nylon 5nm": Nylon filter, manufactured by Pall, pore size 5nm "UPE 1nm": Ultra-high molecular weight polyethylene filter, manufactured by Pall, pore size 1nm "UPE 3nm": Ultra-high molecular weight polyethylene filter, manufactured by Pall, pore size 3nm "UPE 5nm": Ultra-high molecular weight polyethylene filter, manufactured by Pall, pore size 5nm
[0094] <Product to be purified> In order to produce the chemical solutions of the Examples and Comparative Examples, the following organic solvents were used as materials to be purified. ·CyHe: Cyclohexanone ·PGMEA: Propylene glycol monomethyl ether acetate ·MIBC: 4-Methyl-2-pentanol nBA: Butyl acetate EL: Ethyl lactate ·PC: Propylene carbonate IPA: Isopropanol ·PGMEE: Propylene glycol monoethyl ether ·PGMPE: Propylene glycol monopropyl ether CPN: Cyclopentanone In addition, "Raw material 1" to "Raw material 8" in the table indicate that the organic solvents used in each Example and Comparative Example were purchased from the following manufacturers. "Ingredients 1": Honeywell "Raw material 2": Toyo Synthetic "Raw material 3": KH Neochem "Raw material 4": Showa Denko "Raw material 5": KH Neochem "Raw material 6": Sanwa Yuka Kogyo "Raw material 7": CCP "Raw material 8": BASF
[0095] <Container> The following containers were used to store the drug solutions: EP-SUS: A vessel with electrolytically polished stainless steel in contact with the liquid PFA: Container with liquid-contacting parts coated with perfluoroalkoxyalkane The filling rate of each container with the drug solution was 95% by volume (void ratio was 5% by volume). The filling rate is calculated by the following formula: Filling rate = (Volume of drug solution in container / Volume of container) x 100
[0096] <Purification procedure> One of the above-mentioned substances to be purified was selected and subjected to the distillation purification treatment shown in Table 1. In the "Distillation purification" column in the table, "Yes-1" indicates that reduced pressure distillation was performed using a distillation tower (theoretical number of plates: 15), "Yes-2" indicates that reduced pressure distillation was performed twice using a distillation tower (theoretical number of plates: 30), and "Yes-3" indicates that reduced pressure distillation was performed using a distillation tower (theoretical number of plates: 8).
[0097] Next, the distilled and purified product was stored in a storage tank, and the product stored in the storage tank was filtered by passing it through filters 1 to 5 shown in Table 1 in this order, and then stored in the storage tank. Next, the product to be purified stored in the storage tank was filtered through filters 6 and 7 shown in Table 1, and the product to be purified after filtration through filter 7 was circulated upstream of filter 6 and filtered again through filters 6 and 7, thereby carrying out a circulating filtration process. After the circulation and filtration process, the drug solution was placed in a container. In addition, for Examples 85 to 88, water was added to the chemical solution so that the water content was a predetermined value.
[0098] In addition, in the series of purification processes described above, the liquid-contacting parts of various devices (for example, distillation columns, piping, storage tanks, etc.) that come into contact with the purified product were made of electrolytically polished stainless steel.
[0099] The contents of organic components and metal components in the chemical solution were measured by the method described below.
[0100] <Metal component content> The content of metal components (metal ions, metal-containing particles) in the chemical solution was measured by a method using ICP-MS and SP-ICP-MS. The following equipment was used: Manufacturer: PerkinElmer Model: NexION350S The following analysis software was used: ·Syngistix Nano Application Module for “SP-ICP-MS” ·Syngistix for ICP-MS Software However, since metal-containing particles of 10 nm or less cannot be measured by SP-ICP-MS, the above-mentioned identification method was used.
[0101] <Organic impurity content> The content of organic impurities in each drug solution was analyzed using a gas chromatography mass spectrometry (GC / MS) device (Agilent, GC: 7890B, MS: 5977B EI / CI MSD).
[0102] <Test> [Pre-wet or rinsing liquid] The prepared chemical solutions were evaluated for their defect suppression properties when used as a pre-wet solution or a rinsing solution by the method described below. First, the chemical solution was spin-discharged onto a 300 mm diameter silicon substrate or a 300 mm diameter silicon substrate with a silicon oxide film (a silicon substrate whose surface is covered with a silicon oxide film), and while rotating the substrate, 0.5 cc of each chemical solution was discharged onto the surface of the substrate. The substrate was then spin-dried. Next, using a wafer inspection device "SP-5" manufactured by KLA-Tencor, the number of defects present on the substrate after the chemical solution was applied was counted (this was taken as the measured value). Next, using EDAX (energy-dispersive X-ray spectroscopy), the types of defects were classified into metal residue defects, composite residue defects, and stain-like residue defects. Metal residue defects are residues derived from metal components, composite residue defects are residues derived from composites of organic matter and metal components, and stain-like residue defects are residues derived from organic matter. In addition, if both the "metal residue on Si" and the "metal residue on SiO2" are "D" or higher, the liquid is suitable for use as a pre-wet liquid or a rinse liquid.
[0103] <Individual evaluation (metal residue defects, composite residue defects, stain-like residue defects)> A: The corresponding number of defects was 20 or less per board. B: The corresponding number of defects was greater than 20 / substrate and less than or equal to 50 / substrate. C: The corresponding number of defects was greater than 50 / substrate and less than 100 / substrate. D: The corresponding number of defects was greater than 100 / substrate and less than 150 / substrate. E: The number of corresponding defects exceeded 150 / substrate.
[0104] [Developer] The prepared chemical solutions were evaluated when used as developing solutions by the method described below. First, a resist pattern was formed by the following procedure. An actinic ray-sensitive or radiation-sensitive resin composition described below was applied to a silicon substrate having a diameter of 300 mm or a silicon substrate having a diameter of 300 mm with a silicon oxide film, and prebaked (PB) at 100°C for 60 seconds to form a resist film with a thickness of 150 nm.
[0105] (Actinic ray-sensitive or radiation-sensitive resin composition) Acid-decomposable resin (resin represented by the following formula (weight average molecular weight (Mw): 7500): the numerical value written for each repeating unit means mol %): 100 parts by mass
[0106] [ka]
[0107] Photoacid generator as shown below: 8 parts by weight
[0108] [ka]
[0109] Quencher shown below: 5 parts by mass (the mass ratio, from left to right, was 0.1:0.3:0.3:0.2). Of the quenchers shown below, the polymer type quencher has a weight average molecular weight (Mw) of 5000. The numerical values shown for each repeating unit indicate the molar ratio.
[0110] [ka]
[0111] Hydrophobic resin shown below: 4 parts by mass (the mass ratio, from left to right, was 0.5:0.5.) Of the hydrophobic resins shown below, the hydrophobic resin on the left has a weight average molecular weight (Mw) of 7000, and the hydrophobic resin on the right has a weight average molecular weight (Mw) of 8000. In each hydrophobic resin, the numerical value given for each repeating unit means the molar ratio.
[0112] [ka]
[0113] solvent: PGMEA (propylene glycol monomethyl ether acetate): 3 parts by mass Cyclohexanone: 600 parts by mass γ-BL (γ-butyrolactone): 100 parts by mass
[0114] The wafer on which the resist film was formed was scanned with an ArF excimer laser scanner (Numerical Aperture: 0.75) at 25 mJ / cm 2 The wafer was exposed to light at 100°C for 60 seconds. The wafer was then heated at 120°C for 60 seconds. The wafer was then developed by puddling with each developer (chemical) for 30 seconds. The wafer was then rotated at 4000 rpm for 30 seconds to form a negative resist pattern. The resulting negative resist pattern was then heated at 200°C for 300 seconds. Through the above steps, an L / S pattern with a line / space ratio of 1:1 (average pattern width: 45 nm) was obtained. The space portions of the obtained samples were evaluated for the presence or absence of the above-mentioned metal residue defects, composite residue defects, and stain-like residue defects according to the above-mentioned methods.
[0115] In each example, the pressure difference between the filters was 0.01 to 0.03 MPa. In Table 1, "Application 1" in the "Application" column means that the above test was performed using the chemical solution described in each Example and Comparative Example as a pre-wet liquid and a rinse liquid. "Application 2" in the "Application" column means that the above test was performed using the chemical solution described in each Example and Comparative Example as a developer. In the table, "metal residue on Si" shows the evaluation results of metal residue defects on silicon substrates, "composite residue on Si" shows the evaluation results of compound residue defects on silicon substrates, "stain-like residue on Si" shows the evaluation results of stain-like residue defects on silicon substrates, "metal residue on SiO2" shows the evaluation results of metal residue defects on silicon substrates with a silicon oxide film, and "composite residue on SiO2" shows the evaluation results of compound residue defects on silicon substrates with a silicon oxide film.
[0116] In Table 1, the column "Ti oxide particles / Ti ions" indicates the mass ratio of the titanium oxide particle content to the titanium ion content. The column "Ti ion amount (ppt mass)" indicates the titanium ion content (ppt mass) to the total mass of the chemical solution. The column "Fe oxide particles / Fe ions" indicates the mass ratio of the iron oxide particle content to the iron ion content. The column "Fe ion amount (ppt mass)" indicates the iron ion content (ppt mass) to the total mass of the chemical solution. The column "Al oxide particles / Al ions" indicates the mass ratio of the aluminum oxide particle content to the aluminum ion content. The column "Al ion amount (ppt mass)" indicates the aluminum ion content (ppt mass) to the total mass of the chemical solution. The column "Ti oxide particle ratio (% by mass)" indicates the titanium oxide particle content (% by mass) to the titanium component content in the metal component. The column "Fe oxide particle ratio (% by mass)" indicates the iron oxide particle content (% by mass) to the iron component content in the metal component. The "Ratio of Al oxide particles (mass%)" column shows the content (mass%) of aluminum oxide particles relative to the content of aluminum components in the metal components. The "Ratio of Ti oxide particles of 0.5-17 nm (mass%)" column shows the ratio (mass%) of particles with a particle diameter of 0.5 to 17 nm among titanium oxide particles. The "Ratio of Fe oxide particles of 0.5-17 nm (mass%)" column shows the ratio (mass%) of particles with a particle diameter of 0.5 to 17 nm among iron oxide particles. The "Ratio of Al oxide particles of 0.5-17 nm (mass%)" column shows the ratio (mass%) of particles with a particle diameter of 0.5 to 17 nm among aluminum oxide particles. The "Ratio of Cu oxide particles (mass%)" column shows the content (mass%) of copper oxide particles relative to the content of copper components in the metal components. The "Ratio of Cu oxide particles of 0.5-17 nm (mass%)" column shows the ratio (mass%) of particles with a particle diameter of 0.5 to 17 nm among copper oxide particles. The "moisture content" column indicates the water content (mass ppb) in the chemical solution relative to the total mass of the chemical solution. In addition, in Table 1, "E+number" means "10 数字 " For example, "3.5E+04" represents "3.5×10 4 " represents. In Table 1, ">99" means more than 99. "<1" means less than 1. In Table 1, "<500 ppb" means less than 500 ppb by mass.
[0117] [Table 1]
[0118] [Table 2]
[0119] [Table 3]
[0120] [Table 4]
[0121] [Table 5]
[0122] [Table 6]
[0123] [Table 7]
[0124] [Table 8]
[0125] [Table 9]
[0126] [Table 10]
[0127]
Table 11
[0128]
Table 12
[0129]
Table 13
[0130]
Table 14
[0131]
Table 15
[0132]
Table 16
[0133]
Table 17
[0134]
Table 18
[0135]
Table 19
[0136]
Table 20
[0137] [Table 21]
[0138] [Table 22]
[0139] [Table 23]
[0140] [Table 24]
[0141] In Table 1, the data for each Example and Comparative Example are shown in Table 1 [Part 1]. <1> ~ <6> , Table 1 [Part 2] <1> ~ <6> , Table 1 [Part 3] <1> ~ <6> , and Table 1 [Part 4] <1> ~ <6> This is shown across each row. For example, in Example 1, Table 1 [Part 1] <1> As shown in Table 1 [Part 1], CyHe was used as the organic solvent. <2> As shown in Table 1, filter 2 is "IEX 15nm" and <3> As shown in Table 1, the ratio of Ti oxide particles to Ti ions in the solution is 3.5E+04. <4> As shown in Table 1, the amount of Al ions is 32 ppt by mass. <5> As shown in Table 1, the proportion of Fe oxide particles of 0.5-17 nm is 81 mass %. <6> As shown in Fig. 1, "metal residue on Si" is "A". The same is true for the other examples and comparative examples.
[0142] From the results shown in the table, it was confirmed that the chemical solution of the present invention can obtain the desired effects. In particular, from the comparison of Examples 1 to 8, it is clear that the mass ratio of the titanium oxide particle content to the titanium ion content is 10 1 ~10 10 It was confirmed that the effect was more excellent when In addition, from Examples 9 and 10, the mass ratio of the content of iron oxide particles to the content of iron ions was 100 ~10 12 It was confirmed that the effect was more excellent when In addition, from Examples 11 and 12, it was found that the mass ratio of the content of aluminum oxide particles to the content of aluminum ions was 10 0 ~10 12 It was confirmed that the effect was more excellent when Furthermore, it was confirmed from Examples 13 and 14 (34 and 35, 55 and 56, 76 and 77) that the effect was superior when the content of titanium ions (or iron ions, aluminum ions) was 0.10 to 100 ppt by mass relative to the total mass of the chemical solution. Furthermore, it was confirmed from Examples 16 and 17 (37 and 38, 58 and 59, 79 and 80) that the effect was superior when the content of titanium oxide particles (or iron oxide particles, aluminum oxide particles) was 5 mass% or more and less than 99 mass% relative to the content of titanium component in the metal component. Furthermore, from Examples 18 and 19 (39 and 40, 60 and 61, 81 and 82), it was confirmed that the effect is better when the proportion of particles having a particle size of 0.5 to 17 nm among the titanium oxide particles (or iron oxide particles, aluminum oxide particles) is 60 mass % or more and less than 98 mass %. Moreover, it was confirmed from Examples 20 and 21 (41 and 42, 62 and 63, 83 and 84) that the effect was more excellent when the content of organic impurities was 1000 to 100000 ppt by mass relative to the total mass of the chemical solution.
[0143] The chemical solution of Example 22 (100 L) was used to wash the container (EP-SUS) and various devices used in the <Purification Procedure>, and then the chemical solution of Example 22 prepared separately was passed through the above-mentioned washed devices and collected in the washed container, thereby obtaining solution A in the container. In addition, the chemical solution (100 L) of Example 38 was used to wash the container (EP-SUS) and various devices used in the <Purification Procedure>, and then the chemical solution of Example 22, which had been separately prepared, was poured into the above-mentioned washed device and collected in the washed container, thereby obtaining solution B in the container. When "metal residue defects on Si" were evaluated using solutions A and B, better results were obtained with solution A.
[0144] <Example (EUV exposure)> First, resist composition 1 was obtained by mixing the components in the following ratio. ·Resin (A-1): 0.77g Photoacid generator (B-1): 0.03g Basic compound (E-3): 0.03g PGMEA (commercially available, high purity grade): 67.5g Ethyl lactate (commercial product, high purity grade): 75g
[0145] Resin (A-1) As the resin (A-1), the following resin was used.
[0146] [ka]
[0147] Photoacid generator (B-1) As the photoacid generator (B-1), the following compound was used.
[0148] [ka]
[0149] Basic compounds (E-3) As the basic compound (E-3), the following compound was used.
[0150] [ka]
[0151] (Pattern formation and evaluation) First, resist composition 1 was applied onto a silicon wafer having a diameter of 300 mm, and baked at 100° C. for 60 seconds (PB: prebake) to form a resist film with a thickness of 30 nm.
[0152] This resist film was exposed through a reflective mask using an EUV exposure machine (manufactured by ASML; NXE3350, NA 0.33, Dipole 90°, outer sigma 0.87, inner sigma 0.35). Then, it was heated at 85°C for 60 seconds (PEB: Post Exposure Bake). Next, it was developed by spraying a developer (butyl acetate / manufactured by FETW) for 30 seconds by the spray method, and rinsed by discharging a rinse solution onto the silicon wafer for 20 seconds by the spin coating method. Next, the silicon wafer was rotated at a rotation speed of 2000 rpm for 40 seconds to form a line-and-space pattern with a space width of 20 nm and a pattern line width of 15 nm. The rinsing liquids used were the same as those used in Example 44. When the above-mentioned various evaluations were carried out, the desired effects with the same tendencies as those shown in Table 1 were obtained.
Claims
1. a resist film forming step of forming a resist film on a substrate using an actinic ray-sensitive or radiation-sensitive resin composition; an exposure step of exposing the resist film to light; a developing step of developing the exposed resist film to form a resist pattern, at least one selected from the group consisting of a developing solution used in the developing step, a pre-wetting solution used in pre-wetting the substrate before the resist film forming step, and a rinsing solution used in rinsing the substrate having the resist pattern after the developing step is a chemical solution containing an organic solvent and a metal component, The metal component contains titanium oxide particles and titanium ions, The mass ratio of the content of the titanium oxide particles to the content of the titanium ions is 10 1 ~10 7 and The content of the titanium ions is 0.10 to 100 ppt by mass relative to the total mass of the chemical solution.
2. 2. The pattern formation method according to claim 1, wherein the content of said titanium oxide particles is 5% by mass or more and less than 99% by mass with respect to the content of the titanium component in said metal component.
3. 3. The pattern formation method according to claim 1, wherein the proportion of particles having a particle diameter of 0.5 to 17 nm among the titanium oxide particles is 60% by mass or more and less than 98% by mass.
4. The metal component contains iron ions, 4. The pattern formation method according to claim 1, wherein the content of the iron ions is 0.10 to 100 ppt by mass with respect to the total mass of the chemical solution.
5. the metal component comprises iron oxide particles; 5. The pattern formation method according to claim 1, wherein the content of the iron oxide particles is 5% by mass or more and less than 99% by mass with respect to the content of the iron component in the metal component.
6. the metal component comprises iron oxide particles; 6. The pattern formation method according to claim 1, wherein a ratio of particles having a particle diameter of 0.5 to 17 nm to the iron oxide particles is 60% by mass or more and less than 98% by mass.
7. The metal component contains iron oxide particles and iron ions, The mass ratio of the content of the iron oxide particles to the content of the iron ions is 10 0 ~10 12 The pattern forming method according to any one of claims 1 to 6,
8. The metal component contains aluminum ions, 8. The pattern formation method according to claim 1, wherein the content of the aluminum ions is 0.10 to 100 ppt by mass with respect to the total mass of the chemical solution.
9. the metal component contains aluminum oxide particles; 9. The pattern formation method according to claim 1, wherein the content of the aluminum oxide particles is 5% by mass or more and less than 99% by mass with respect to the content of the aluminum component in the metal component.
10. the metal component contains aluminum oxide particles; The chemical solution according to any one of claims 1 to 9, wherein a ratio of particles having a particle diameter of 0.5 to 17 nm among the aluminum oxide particles is 60 mass % or more and less than 98 mass %.
11. The metal component contains aluminum oxide particles and aluminum ions, The mass ratio of the content of the aluminum oxide particles to the content of the aluminum ions is 10 0 ~10 12 The pattern forming method according to any one of claims 1 to 10,
12. The metal component contains copper oxide particles, The pattern forming method according to any one of claims 1 to 11, wherein the content of the copper oxide particles is 5 mass % or more and less than 99 mass % with respect to the content of the copper component in the metal component.
13. The metal component contains copper oxide particles, The pattern formation method according to any one of claims 1 to 12, wherein a ratio of particles having a particle diameter of 0.5 to 17 nm to the copper oxide particles is 60 mass % or more and less than 98 mass %.
14. The metal component contains copper oxide particles and copper ions, The mass ratio of the content of the copper oxide particles to the content of the copper ions is 10 0 ~10 12 The pattern forming method according to any one of claims 1 to 13,
15. a resist film forming step of forming a resist film on a substrate using an actinic ray-sensitive or radiation-sensitive resin composition; an exposure step of exposing the resist film to light; a developing step of developing the exposed resist film to form a resist pattern, at least one selected from the group consisting of a developing solution used in the developing step, a pre-wetting solution used in pre-wetting the substrate before the resist film forming step, and a rinsing solution used in rinsing the substrate having the resist pattern after the developing step is a chemical solution containing an organic solvent and a metal component, the metal component contains titanium oxide particles, titanium ions, iron ions, iron oxide particles, aluminum ions, aluminum oxide particles, copper oxide particles, and copper ions; The mass ratio of the content of the titanium oxide particles to the content of the titanium ions is 10 0 ~10 7 and The content of the titanium ion is 0.10 to 100 ppt by mass relative to the total mass of the chemical solution, The content of the iron ions is 0.10 to 100 ppt by mass relative to the total mass of the chemical solution, the content of the iron oxide particles is 5% by mass or more and less than 99% by mass with respect to the content of the iron component in the metal component, The content of the aluminum ions is 0.10 to 100 ppt by mass relative to the total mass of the chemical solution, the content of the aluminum oxide particles is 5% by mass or more and less than 99% by mass with respect to the content of the aluminum component in the metal component, The content of the copper oxide particles is 5% by mass or more and less than 99% by mass with respect to the content of the copper component in the metal component, The mass ratio of the content of the copper oxide particles to the content of the copper ions is 10 0 ~10 12 The pattern forming method is as follows.
16. In addition, it contains organic impurities, 16. The pattern formation method according to claim 1, wherein the content of the organic impurities is 1,000 to 100,000 ppt by mass with respect to the total mass of the chemical solution.
17. The pattern formation method according to any one of claims 1 to 16, wherein the content of water relative to the total mass of the chemical solution is 500 ppb by mass or less.
18. The pattern formation method according to any one of claims 1 to 17, wherein the organic solvent comprises at least one selected from the group consisting of propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, cyclohexanone, ethyl lactate, propylene carbonate, isopropanol, 4-methyl-2-pentanol, butyl acetate, propylene glycol monoethyl ether, propylene glycol monopropyl ether, methyl methoxypropionate, cyclopentanone, γ-butyrolactone, diisoamyl ether, isoamyl acetate, dimethyl sulfoxide, N-methylpyrrolidone, diethylene glycol, ethylene glycol, dipropylene glycol, propylene glycol, ethylene carbonate, sulfolane, cycloheptanone, 2-heptanone, butyl butyrate, isobutyl isobutyrate, isoamyl ether, and undecane.
19. the organic solvent is butyl acetate; The pattern formation method according to any one of claims 1 to 18, wherein the developer is the chemical solution.
20. a resist film forming step of forming a resist film on a substrate using an actinic ray-sensitive or radiation-sensitive resin composition; an exposure step of exposing the resist film to light; a developing step of developing the exposed resist film to form a resist pattern, The developer used in the developing step is a chemical solution containing an organic solvent and a metal component, the organic solvent is butyl acetate; The metal component contains titanium oxide particles and titanium ions, The mass ratio of the content of the titanium oxide particles to the content of the titanium ions is 10 0 ~10 7 and The content of the titanium ions is 0.10 to 100 ppt by mass relative to the total mass of the chemical solution.
21. the organic solvent comprises at least one selected from the group consisting of propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether, cyclohexanone, ethyl lactate, propylene carbonate, isopropanol, 4-methyl-2-pentanol, propylene glycol monopropyl ether, methyl methoxypropionate, cyclopentanone, γ-butyrolactone, diisoamyl ether, isoamyl acetate, dimethyl sulfoxide, N-methylpyrrolidone, diethylene glycol, ethylene glycol, dipropylene glycol, propylene glycol, ethylene carbonate, sulfolane, cycloheptanone, 2-heptanone, butyl butyrate, isobutyl isobutyrate, isoamyl ether, and undecane; The pattern formation method according to any one of claims 1 to 18, wherein the pre-wet liquid or the rinsing liquid is the chemical liquid.
Citation Information
Patent Citations
Organic process liquid for patterning chemically amplified resist film
JP2015084122A
Method for manufacturing chemical solution for manufacturing electronic material, pattern forming method, method for manufacturing semiconductor device, chemical solution for manufacturing electronic device, container, and quality inspection method
WO2017170428A1
Processing liquid and processing liquid container
WO2017188296A1
Method for manufacturing liquid medicine and device for manufacturing liquid medicine
WO2018142888A1